A facile synthesis of 1, 3, 6, 8-pyrenesulfonic acid tetrasodium salt as a hydrosoluble fluorescent ink for anti-counterfeiting applications. Issue 1 (2nd January 2019) - Chen, Liangzhe; Hu, Biao; Zhang, Jieyu; Zhang, Jinmei; Huang, Shuting; Ren, Ping; Zou, Yang; Ding, Fuyuan; Liu, Xinghai; Li, Houbin
Abstract : In this work, 1, 3, 6, 8-pyrenesulfonic acid sodium salt (PTSA) was successfully synthesized via a one-step sulfonating reaction and exhibited the potential in anti-counterfeiting. Abstract : In this work, 1, 3, 6, 8-pyrenesulfonic acid sodium salt (PTSA) was successfully synthesized via a one-step sulfonating reaction. This method is more convenient, effective and eco-friendly than the traditional one. The as-prepared PTSA exhibits pure blue fluorescence under UV light. Due to its excellent fluorescent properties and water solubility, PTSA was used to prepare water-soluble invisible inks based on hydroxyethyl cellulose (HEC) aqueous solution. Notably, the resulting inks possessed acceptable stability after being stored for 30 days. Besides, the red/green/blue fluorescent inks were obtained by adding extra pigments, all of which exhibited excellent rheology and thixotropy properties. Subsequently, various patterns, including a QR code, the logo of Wuhan University, Chinese characters and so on, were printed on non-background paper through ink-jet and screen printing, and the as-prepared materials exhibited good water solubility and outstanding fluorescence performances, indicating that the fluorescent PTSA material is a promising candidate for anti-counterfeiting applications.